Autologous Fat Grafting for Treating Blepharoplasty-induced Lower Eyelid Retraction. Issue 12 (December 2016) - Skippen, Brent; Bernardini, Francesco P.; Fezza, John; Hartstein, Morris E.
Abstract : Summary: Autologous fat grafting for blepharoplasty-induced lower eyelid retraction offers potential for a long-term solution while avoiding the morbidity associated with posterior lamellar spacer grafts. By combining traditional methods of lifting the retracted lower eyelid with autologous fat grafting, both functional and aesthetic concerns can be successfully addressed in these patients.